PENGARUH MODEL CONCEPT ATTAINMENT TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA MATA PELAJARAN BIOLOGI MATERI SISTEM PENCERNAAN - Marzuki Marzuki (Jurnal Dedikasi Pendidikan, 2024)
This learning model for achieving the Concept Attainment concept aims to develop social processes and create principles that are understood by students by carrying out activities with special emphasis placed on understanding facts, events, laws and principles. This research aims to determine: Student activities before and after implementing the concept achievement learning model. To determine student learning outcomes before and after implementing the concept achievement learning model and to determine the influence of the concept achievement learning model on learning activities in class VIII D of SMPN 1 Ambalau. This research method uses quantitative research methods. The form of research is Quasi Experimental Design. The research design uses One Group Pretest Posttest Design. The data collection technique is carried out using multiple choice test questions, namely in the form of a learning outcomes test, documentation techniques in the form of research drawings and photos as well as value documents related to the results. Data analysis using the t test. In the hypothesis test, the data obtained was t count > t table, namely 2.82 > 2.70. H0 is rejected and H1 is accepted, meaning that the Concept Attainment learning model can have a significant influence on student activities and learning outcomes. Based on statistical results, it is known that the influence of the Concept Attainment learning model on student activities and learning outcomes is (d) 1.94, which is included in the large/high category.